Contaminación del aire por el uso de plaguicidas en bananeras y su impacto en la salud humana. - Saltos Saltos, Angel David (Machala : Universidad Técnica de Machala, 2022)
Banana production in Ecuador occupies one of the main incomes because it is a very desirable fruit in the world and for its production it requires the use of pesticides to have a pest control typical of this agricultural activity, in this the pesticides that are used are under the monitoring of Agrocalidad, an institution attached to the Ministry of the Environment and the National Directorate of Surveillance and Sanitary Control of the Ministry of Health. These pesticides, which can be insecticides, herbicides, fungicides, must be supplied under certain parameters, but with demographic growth in many cases, such as in the province of El Oro, the community settlements settle next to the banana plantations due to the lack of housing. dependent on this activity itself, in this there is an exposure to these agrochemicals that produce health effects such as neurotoxicity, carcinogenic effects, dermatological, hematopoietic effects and more side effects for which it is advisable to consider other alternatives to this problem such as organic production, the use of organic insecticides, chain cultivation, declaration of non-developable areas in places adjacent to the banana plantations. The present investigation is of a bibliographical type, since it is based on the review of scientific and institutional sources related to the banana activity, in addition to an interview with an Agrocalidad technician to contrast the information investigated. It is recommended to take preventive health measures as well as to regulate and plan settlements by the local council in the case of Machala.
La producción bananera en Ecuador ocupa uno de los principales ingresos por ser una fruta muy apetecida en el mundo y para su producción requiere hacer uso de plaguicidas para tener un control de plagas propia de esta actividad agrícola, en ello los plaguicidas que se emplean están bajo el monitoreo de Agrocalidad una institución adscrita al Ministerio del Ambiente y la Dirección Nacional de Vigilancia y Control Sanitario del Ministerio Salud. Estos plaguicidas que pueden son insecticidas, herbicidas, fungicidas deben ser suministrados bajo ciertos parámetros pero con el crecimiento demográfico en muchos casos como en la provincia de El Oro los asentamientos comunitarios se posan junto a las bananeras ante la falta de una vivienda a más de ser dependientes de esta actividad propiamente dicha, en ello se produce una exposición a estos agroquímicos que producen efectos en la salud como neurotoxicidad, efectos cancerígenos, afectaciones dermatológicas, hematopoyética y más efectos secundarios que para los que es recomendable considerar otras alternativas a esta problemática como la producción orgánica, el uso de insecticidas orgánicos, cultivo en cadena, declaratoria de zonas no urbanizables en lugares colindantes a las bananeras. La presente investigación es de tipo bibliográfica al basarse en la revisión de fuentes científicas e institucionales afines a la actividad bananera a más de entrevista a un técnico de Agrocalidad para contrastar la información indagada. Se recomienda tomar las medidas preventivas de salud así como regular y planificar los asentamientos por parte del cabildo local en el caso de Machala.
Keywords: ALTERNATIVAS; FUMIGACIONES; PLAGUICIDAS; PRODUCCION BANANERA